2009
DOI: 10.1002/cncr.24577
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparity in the rate of partner abandonment in patients with serious medical illness

Abstract: The demand for increased formulation concentrations for protein therapeutics puts a significant strain on already existing tangential flow filtration (TFF) systems that were constructed with lower protein concentration targets as part of their design criteria. TFF is commonly used to buffer exchange and concentrate the product to the appropriate drug substance concentration. Analyzing the ability of an existing TFF system to process under conditions outside its original design specifications can be challenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
4
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 31 publications
5
68
4
4
Order By: Relevance
“…[34][35][36][37] Professional support for patients and for family and friends can reduce the burden on both. 35,38,39 Empathetic physicians, nurses, and/or social workers may offer support in coping with MS and its consequences.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37] Professional support for patients and for family and friends can reduce the burden on both. 35,38,39 Empathetic physicians, nurses, and/or social workers may offer support in coping with MS and its consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The overall frequency of divorce was 32.1%, which is much higher than the overall divorce rate of 2.4 per 1,000 individuals in Korea in 2012 (Statistics Korea, 2014). This rate was also higher than that found in prior studies, which suggested that the overall frequency of divorce among cancer patients is in the 5-17% range (Glantz et al, 2009). Prior studies have shown that a cancer diagnosis can bring increased marital distress (Hassali et al, 2013;Kirchhoff et al, 2012).…”
Section: Discussionmentioning
confidence: 63%
“…In a recent survey of brain tumor survivors, nearly 70% were unable to return to previous employment and the majority remained unemployed. Another study discussed the gender disparity in the rate of partner abandonment in patients with cancer [31].…”
Section: Radiotherapymentioning
confidence: 99%